penelitian PERSEPSI ORANG TUA TENTANG PEMBELAJARAN DARING MASA PANDEMI COVID-19: PADA SISWA KELAS IV,V, DAN VI DI SEKOLAH DASAR NEGERI 1 SENDEN KECAMATAN KAMPAK KABUPATEN TRENGGALEK - Dodik Wibowo; Lilik Setyawan; Ariani Sulistyorini (STIKES dan AKZI Karya Husada Kediri, 2022)
Online learning during the Covid-19 pandemic becomes a transformation for the learning system to reduce the spread of Covid-19. The development ability of students becomes the main task of parents, so the perception of parents is very influential in online learning success. The perception of parents of online learning is various because online learning is a new thing applied. Perception is known as the way a person recognizes understand interprets and composes absorbed information obtained by the senses as a form of subjective response. The purpose of this research is to know the perception of parents about online learning during the Covid-19 pandemic in IV, V, and VI classes. This research uses a descriptive, population and sample are 26 respondents, using a total sampling technique, an instrument of research using a questionnaire sheet, research is implemented from 29th February- 12th March 2022. The variable of research is the perception of parents about online learning during the Covid-19 pandemic in IV, V, and VI classes. Data were analyzed using the mean formula and interpreted quantitatively. Results of research obtained from 26 respondents show that most of the respondents have negative perceptions 16 respondents (62%) and almost half of the respondents have positive perceptions 10 respondents (38%). Perceptions of parents in online learning is influenced by some factor, that as education, accompanying children in studying, and age. Hope that respondents can have positive perceptions by increasing knowledge about online learning and it is hoped that the school provides education to parents about the benefits of online learning during the covid-19 pandemics so that parents do not have negative perceptions about online learning